A Rare Case of Dacryocystocele Diagnosed by Antenatal Ultrasonography at 26 Weeks of Gestation - Ganesan, Parvathy; Balakrishnan, Bijoy K.; Parasuram, Meenu Batra (Journal of Fetal Medicine, 2023)
Dacryocystocele is a rare variant of obstruction of the nasolacrimal duct that results in a fluid-filled, closed sac. It often resolves by the spontaneous perforation of the distal membrane during the early neonatal period, resulting in drainage of the accumulated fluid. If persisting, this benign condition can be usually treated postnatally. If the cysts occur bilaterally, there can be an obstruction to the nasal passage due to their possible intranasal extension and might require surgical intervention postnatally to prevent or treat respiratory distress. Also, it may be a part of a few syndromes, which makes the early prenatal diagnosis very important. In this case report, we present a case of unilateral dacryocystocele reported as early as 26 weeks, 3 days of gestation detected by ultrasound that spontaneously resolved by 33 weeks. This is one of the earliest reported three-dimensional/four-dimensional ultrasound diagnosis of dacryocystocele.
Keywords: dacryocyctocele; prenatal diagnosis; Inner canthus; inferomedial; complete resolution